Effects of di-(2-ethylhexyl) phthalate on growth, metabolism, and virulence of the plant pathogenic bacterium Acidovorax citrulli - Kim, Yu-Ri; Sang, Mee Kyung (Frontiers in Cellular and Infection Microbiology, 2023)
Acidovorax citrulli is a seed-borne bacterial pathogen that causes bacterial fruit blotch in cucurbits and severely affects the production of cucumbers and watermelons globally. In this study, we investigated the effects of di-(2-ethylhexyl) phthalate (DEHP) on the growth, metabolism, and virulence of A. citrulli. Bacterial population was not affected by DEHP exposure; moreover, significant changes were not observed in lipid peroxidation, membrane permeability, and nucleic acid leakage. However, palmitoleic acid content was increased in the cell membrane of DEHP-exposed A. citrulli. Further, DEHP exposure increased the activity of TCA cycle-related enzymes, including α-ketoglutarate dehydrogenase and succinyl-CoA synthetase, along with increase in the content of glutamate, succinate, fumarate, and malate in TCA cycle. Additionally, total 270 genes were differentially expressed by the treatment, of which 28 genes were upregulated and 242 genes, including those related to translation, flagellum-dependent cell motility, and flagellum assembly, were downregulated. Regarding virulence traits, swimming activity was decreased in DEHP-exposed A. citrulli; however, biofilm formation was not affected in in vitro assay. Moreover, relative expression of pathogenicity genes, including hrpX and hrpG, were decreased in DEHP-exposed A. citrulli compared to that of unexposed A. citrulli. Therefore, these results suggest that DEHP accumulation in soil could potentially influence the metabolism and virulence traits of A. citrulli.